176k views
1 vote
Simplify the expression
5 + 3w+3 - W
12W
8 + 2
02w - 8

User Will Holtz
by
5.6k points

2 Answers

7 votes

Explanation:

Simplifying

5 + 3w + 3 + -1w = 0

Reorder the terms:

5 + 3 + 3w + -1w = 0

Combine like terms: 5 + 3 = 8

8 + 3w + -1w = 0

Combine like terms: 3w + -1w = 2w

8 + 2w = 0

Solving

8 + 2w = 0

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-8' to each side of the equation.

8 + -8 + 2w = 0 + -8

Combine like terms: 8 + -8 = 0

0 + 2w = 0 + -8

2w = 0 + -8

Combine like terms: 0 + -8 = -8

2w = -8

Divide each side by '2'.

w = -4

Simplifying

w = -4

User Puppybits
by
4.9k points
3 votes
if you’re simplifying that expression, it should be 2W+8.
User Timur Mingulov
by
5.0k points